Pengetahuan Berhubungan dengan Sikap Ibu dalam Kemampuan Menstimulasi Pertumbuhan dan Perkembangan Anak Balita dengan Gizi Kurang - Sulistyawati Sulistyawati; M Ros Mistyca (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
Nutrition is an important factor in determining the level of health. The state of malnutrition in children results in impaired growth and development of children. Knowledge or cognitive domain is very important for the formation of maternal attitudes and actions in stimulating the growth and development of children. Children who are directed stimulation will grow faster than children who did not receive stimulation. The purpose of study is to know the relationship of knowledge with mother attitude in the ability to stimulating growth and development of young children with less nutrition in Banaran village work area Galur II Health Centers Kulon Progo Yogyakarta. This type of research is an analytic survey, with the cross sectional approach. The sampling technique is purposive sampling, with 43 respondents. Bivariate analysis used Spearman Rank correlation. The results showed the knowledge of mothers with 25.6% in good category category, 67.4% in enough category, and 7,0% in less category. While the mother’s attitude showed 18.6% in good categories, and 81.4% in enough category. The results of the statistical test showed r=0.467 with a significance level of correlation coefficient 0.002. Conclusion, the research indicated that significant relationship between knowledge with mother attitude in the ability to stimulating growth and development of young children with less nutrition in Banaran village work area Galur II Health Centers Kulon Progo Yogyakarta.